Disturbing Times Medieval Pasts, Reimagined Futures - Karkov, Catherine; klosowska, anna; van Gerven Oei, Vincent W.J (punctum books, 2020)
"From Kehinde Wiley to W.E.B. Du Bois, from Nubia to Cuba, Willie Doherty's terror in ancient landscapes to the violence of institutional Neo-Gothic, Reagan's AIDS policies to Beowulf fanfiction, this richly diverse volume brings together art historians and literature scholars to articulate a more inclusive, intersectional medieval studies. It will be of interest to students working on the diaspora and migration, white settler colonialism and pogroms, Indigenous studies and decolonial methodology, slavery, genocide, and culturecide. The authors confront the often disturbing legacies of medieval studies and its current failures to own up to those, and also analyze fascist, nationalist, colonialist, anti-Semitic, and other ideologies to which the medieval has been and is yoked, collectively formulating concrete ethical choices and aims for future research and teaching. In the face of rising global fascism and related ideological mobilizations, contemporary and past, and of cultural heritage and history as weapons of symbolic and physical oppression, this volume's chapters on Byzantium, Medieval Nubia, Old English, Hebrew, Old French, Occitan, and American and European medievalisms examine how educational institutions, museums, universities, and individuals are shaped by ethics and various ideologies in research, collecting, and teaching."